2003
DOI: 10.1021/es020196y
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Gradients of Polycyclic Aromatic Hydrocarbon (PAH) Dissipation in Two Industrial Soils and the Impact of Arbuscular Mycorrhiza

Abstract: Phytoremediation of organic pollutants depends on plant-microbe interactions in the rhizosphere, but the extent and intensity of such rhizosphere effects are likely to decrease with increasing distance from the root surface. We conducted a time-course pot experiment to measure dissipation of polycyclic aromatic hydrocarbons (PAHs) in the rhizosphere of clover and ryegrass grown together on two industrially polluted soils (containing 0.4 and 2 g kg(-1) of 12 PAHs). The impact of the fungal root symbiosis arbusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
132
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(148 citation statements)
references
References 49 publications
10
132
0
6
Order By: Relevance
“…Phytoremediation of organic pollutants depends on plante microbe interactions in the rhizosphere (Joner and Leyval, 2003b). We observed a pronounced influence of the AM fungus on soil microbial abundance.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Phytoremediation of organic pollutants depends on plante microbe interactions in the rhizosphere (Joner and Leyval, 2003b). We observed a pronounced influence of the AM fungus on soil microbial abundance.…”
Section: Discussionmentioning
confidence: 71%
“…Research has established that AM fungi can enhance the growth of several plant species in soil with high polycyclic aromatic hydrocarbon (PAH) concentrations (Leyval and Binet, 1998). Experimental evidence has been obtained for the impact of AM on the uptake and dissipation of some organic pollutants in soil such as PAHs and atrazine (Joner and Leyval, 2003b;Huang et al, 2007). These studies indicated that AM fungi conferred some benefit on phytoremediation of soils contaminated with organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential role of AM in the phytoremediation of soils with organic contaminants, very few studies have been carried out on interactions between AM and organic pollutants such as PAHs in soil and variable results have been obtained. Positive effects of AM on the dissipation of PAHs in soils have been observed by Joner et al (Joner and Leyval, 2003;Joner et al, 2001). In contrast, no impact of AM fungi on PAH dissipation was observed by Binet et al (2000) and a depression in PAH dissipation was observed in the presence of ectomycorrhizas (Joner et al, 2006;Genney et al, 2004).…”
Section: Introductionmentioning
confidence: 79%
“…Arbuscular mycorrhiza (AM) is a ubiquitous association between soil fungi and the roots of most herbaceous plant species that permits the host plant to exploit nutrients in the soil beyond the rhizosphere through fungal transport (Joner and Leyval, 2003). Mycorrhizal colonization can result in quantitative and qualitative changes in root exudation and in the soil microbial community, particularly in the rhizosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that only the metabolites DEA and DIA were detected in the plant roots could contribute to the important role of the plant-derived enzymes in roots in degradation and then the metabolites assimilated into the plant tissue (Boyajian and Carriera, 1997). AM fungi were reported to obligate symbionts with little or no capacity for degradation of organics (Joner and Leyval, 2003b). Therefore, the increasing enzyme activity and microorganism stimulated by colonization was the possible reason for the enhanced metabolism in mycorrhizal colonized roots.…”
Section: Discussionmentioning
confidence: 99%